2000
DOI: 10.3168/jds.s0022-0302(00)75064-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Season on Proteolysis and Sensory Characteristics of Idiazabal Cheese

Abstract: The present study examined the influence of the manufacturing time on proteolysis and sensory characteristics of Idiazabal cheese. Samples of Idiazabal cheeses made using traditional manufacturing methods at two different times of year were collected at a plant operating under the auspices of the Idiazabal Cheese Appellation of Origin. The cheeses were made in February and June, roughly the beginning and the end of the manufacturing season. Chemical analyses were performed on d 1, 90, and 180 of ripening and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
7
21
0
2
Order By: Relevance
“…Other authors have reported that the WSN and the PTASN fractions are mainly responsible for cheese flavour (Aston & Creamer, 1986;Aston, Durward, & Dulley, 1983a, Aston, Grieve, Durward, & Dulley, 1983b. Mendía, Ibáñ ez, Torre, and Barcina (2000) found that Idiazábal cheeses with a more intense degradation of the a s -and b-caseins and higher levels of nitrogen fractions and free amino acids, obtained higher scores for the characteristic olfative and gustative attributes. We can conclude that the highest scores for the gustative attributes were obtained for artisanal cheeses, and were related to a heterogeneous microflora and a complex enzymatic system and to high contents of nitrogen fractions.…”
Section: Descriptive Sensory Analysismentioning
confidence: 97%
“…Other authors have reported that the WSN and the PTASN fractions are mainly responsible for cheese flavour (Aston & Creamer, 1986;Aston, Durward, & Dulley, 1983a, Aston, Grieve, Durward, & Dulley, 1983b. Mendía, Ibáñ ez, Torre, and Barcina (2000) found that Idiazábal cheeses with a more intense degradation of the a s -and b-caseins and higher levels of nitrogen fractions and free amino acids, obtained higher scores for the characteristic olfative and gustative attributes. We can conclude that the highest scores for the gustative attributes were obtained for artisanal cheeses, and were related to a heterogeneous microflora and a complex enzymatic system and to high contents of nitrogen fractions.…”
Section: Descriptive Sensory Analysismentioning
confidence: 97%
“…It is well accepted that the amount of total, hydrophobic and hydrophilic peptides and the hydrophobic:hydrophilic ratio is a suitable way to study the proteolysis process and the changes in these parameters were significantly influenced by cheese age (Mallatou et al 2004;Picon et al 2007;Tejada et al 2008). Seasonal changes in milk composition affect cheese yield, quality and sensory characteristics (Izco & Torre 2000;Mendía et al 2000;Fernández-García et al 2004a, b, 2006Muñoz et al 2003;). Changes in cheese yield (due to increases in the concentrations of milk fat and protein ) and the lipolytic activity and microbiological quality of bulk raw ewe's milk are the main aspects affected seasonaly during the cheese-making period (Barron et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the sensory characteristics of Idiazabal cheese have found differences in odour and flavour attributes among cheeses made at different times of the year. 27,28 To the best of our knowledge, detailed data about the volatile composition of Idiazabal cheese has not been published. Larráyoz et al 29 identified 26 compounds in the volatile fraction of the Idiazabal cheese by comparing the retention times of unknown compounds with those of known compounds using GC-FID.…”
Section: Introductionmentioning
confidence: 99%